The determinants of trade and trade direction of Arab Maghreb Union (AMU) - Abdullah, Norehan; Abdullah, Hussin; Abuhriba, Hadi M. Othman (Research Academy of Social Sciences (RASS), 2015)
The Arab Maghreb Union (AMU) comprising Algeria, Libya, Mauritania, Morocco, and Tunisia have established a framework to enhance regional cooperation on trade facilitation.Today, the AMU countries have increased their trade integration into the world economy.Despite the effort of trade openness in the AMU, the economic growth, intra-trade and inter-trade are still lagging behind other developing countries in the Middle East, Asia, and Latin America.The paper examines the determinants of intra-regional trade in the AMU countries.Using a data set of 1989-2009; the standard gravity model is used to measure the pattern and trend of bilateral trade.Overall, the results are consistent with those found in previous study where in all cases, parameters for the variables are found to be correctly signed and highly significant.A higher GDP increases trade while a longer distance inhibits trade.Larger population also results in higher trade.In terms of trade openness, the results show that the trade barriers are found to be positively and significantly correlated with openness.In short, the trade barriers are fairly effective for increasing trade